Monocyte CD36 Expression Predicts Disease Activity in Patients With Crohn’s Disease - Jiejie Zhu; Nannan Zhu; Jiren Wang; Qiuyuan Liu; Qiao Mei (Gastroenterology Research and Practice)
Conclusions: These data indicate that monocyte CD36 associates with disease activity in CD and might be a potential biomarker for assessing the activity of CD.